The Effect of Freezing and Refrigeration on Food Quality - Remington, Mary Catherine Anne (Clemson University Libraries, 2017)
Food shelf-life extension is important not only to food manufacturers, but also to home refrigeration/freezing appliance companies, whose products affect food quality and food waste. While freezing and refrigerating both extend the shelf life of foods, food quality deterioration continues regardless of the preservation method. Quality attributes of frozen Atlantic salmon (Salmo Salar) were analyzed at different freezing rates to core holding temperatures of -106°F/-77°C, -20°F/-29°C, 0°F/-18°C, 10°F/-12°C, and 20°F/-7°C. Quality measurements that were traced included total weight loss after freezing, thawing, and cooking, change in color and texture, freezing and thawing rates, as well ice crystal pore analysis. The overall objective of the freezing study was to determine if freezing rates had measurable effects on food quality so that more energy efficient freezer temperature ranges could be used while also minimizing damage to food quality. Samples frozen at faster freezing rates had lower mass loss than samples frozen at higher freezing rates. Salmon frozen at higher freezing rates also had much lighter (L*) than samples frozen at slower freezing rates. Color difference (∆E) decreased amongst frozen samples frozen at higher freezing rates when compared to a control frozen Atlantic salmon sample (change for new ∆E values). Readings of maximum force from texture analysis also varied between frozen samples frozen at different rates based upon Muellenet-Owens razor shear blade and Warner-Bratzler shear force analysis. Surface ice crystal pore size decreased with an increase in freezing rate in samples, while total number of pores increased with an increase freezing rate.